Pengembangan perangkat pembelajaran skala pada denah berbasis masalah untuk meningkatkan kemampuan pemecahan masalah - Diniyah, Eka Nuhayati; Wiryanto, Wiryanto; Ekawati, Rooselyna; Hendratno, Hendratno (Program Studi Pendidikan Matematika, Universitas Nusantara PGRI Kediri, 2021)
This study aims to describe the process of developing problem-based learning, analyze the results of the device development, describe student's problem solving with problem-based learning on the scale materials on the map. This research uses research and development (R&D) type, namely 4D-Model (Define, Design, Develop, and Disseminate). The developed learning tools are including; lesson plans (RPP), LKPD, and a problem-solving ability test (KPM). The results of the development of the scale learning device on the map is valid, practical and effective. The validity of the learning tools is as follows: the average RPP validation is 3.68 or 91.91% in the valid category; LKPD of 3.39 or 84.75% in the valid category; and the KPM test of 3.12 or 78% in the valid category. Therefore, based on the results of the assessment of the validator, problem-based learning tools can be used for learning activities. Practicality of learning tools: the ability of teachers to manage learning is 3.48 or the percentage of implementation is 87% with the category of good implementation; student activity in learning activities is 97.5%. Therefore, it could be claimed as effective. The effectiveness of learning tools: the percentage of changes in KPM of positive students is 75%; the increase in KPM gets an N-Gain score of 0.59 in the medium category, the completeness of percentage in classical learning is 90% thus, it could be claimed as complete, while the student response in positive learning is in an average score of 97 %. Based on the results of the research on the learning device scale on the problem-based map based on good criteria which is valid, practical and effective so that it can be used for learning activities.